Beberapa Oligomer Stilbenoid dari Tumbuhan Shorea multiflora Burck - Noviany Noviany; Euis Holisotan Hakim; Sjamsul Arifin Achmad; Yana Maolana Syah; Lia Dewi Juliawaty; Norio Aimi; Emilio L Ghisalberti; Iqbal M. Choudhary (Institut Teknologi Bandung, 2003)
Two dimers of stilbenoids, (-)-balanocarpol (4), and (-)-ampelopsin A (5), along with a tetramer (-)-hopeaphenol (6) were isolated from the stem bark of Shorea multiflora Burck (Dipterocarpaceae), locally known as Meranti. Their structures were determined by physical and UV, IR, 1H-NMR, and 13C-NMR spectroscopic data.